2015
DOI: 10.3945/jn.115.218636
|View full text |Cite
|
Sign up to set email alerts
|

The Homozygous Hemoglobin EE Genotype and Chronic Inflammation Are Associated with High Serum Ferritin and Soluble Transferrin Receptor Concentrations among Women in Rural Cambodia

Abstract: Compared with sTfR, ferritin concentrations appear to reflect more accurately true ID in rural Cambodian women. The CFs from a published meta-analysis were appropriate for use in this population with a high prevalence of Hb disorders and inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
1
10
1
Order By: Relevance
“…We found a large difference in estimated prevalence of ID based on sTfR and SF, even after 334 adjustment, which is consistent with findings of other studies (10,14,22,39,40). Since SF and 335 sTfR measure different aspects of iron status, differences in prevalence may not be surprising.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…We found a large difference in estimated prevalence of ID based on sTfR and SF, even after 334 adjustment, which is consistent with findings of other studies (10,14,22,39,40). Since SF and 335 sTfR measure different aspects of iron status, differences in prevalence may not be surprising.…”
supporting
confidence: 80%
“…However, as previously mentioned in contrast to our results others have observed positive 322 relationships between inflammation markers and sTfR (10)(11)(12)(13)(14) or shown that that sTfR 323 decreased in malaria (8). In addition to increased erythropoiesis, higher sTFR concentrations 324 in children with infections may also be due to poorer iron status.…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…Furthermore, menstrual blood loss, a determinant of iron stores in women of reproductive age [38], was not recorded. Inherited hemoglobin disorders are also known to impact on iron markers [27,39]. Recently, these effects were examined in a cross-sectional survey among 450 Cambodian women [39].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we used Thurnham et al [19] correction factors to adjust for levels of inflammation in our populations studied. These correction factors were demonstrated to be accurate for use in the same Cambodian population of n = 420 women in this study (which also used the s-ELISA to measure the inflammation biomarkers used for adjustments) [27], however, the robustness of these correction factors for use with the other ferritin assays has not yet been established.…”
Section: Limitations Of Our Studymentioning
confidence: 99%